2007
DOI: 10.1038/sj.jcbfm.9600577
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-Gated K+ Channel Dysfunction in Myocytes from a Dog Model of Subarachnoid Hemorrhage

Abstract: Delayed cerebral vasospasm after subarachnoid hemorrhage is primarily due to sustained contraction of arterial smooth muscle cells. Its pathogenesis remains unclear. The degree of arterial constriction is regulated by membrane potential that in turn is determined predominately by K+ conductance (GK). Here, we identified the main voltage-gated K+ (Kv) channels contributing to outward delayed rectifier currents in dog basilar artery smooth muscle as Kv2 class through a combination of electrophysiological and pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 45 publications
5
29
0
1
Order By: Relevance
“…For example, inwardly rectifying K + channels were increased during vasospasm after SAH, suggesting one possible mechanism for such reversal [20]. Another is that the decrease in K V channel function does not cause vasospasm, although function studies suggested that this is not the case [6]. Also, studies reported that vasospasm in rabbits was decreased with K + channel agonists [9;10;23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, inwardly rectifying K + channels were increased during vasospasm after SAH, suggesting one possible mechanism for such reversal [20]. Another is that the decrease in K V channel function does not cause vasospasm, although function studies suggested that this is not the case [6]. Also, studies reported that vasospasm in rabbits was decreased with K + channel agonists [9;10;23].…”
Section: Discussionmentioning
confidence: 99%
“…We previously characterized K V current (IK V ) from dog basilar artery and validated protocols to characterize these currents [6]. The same protocols were used in the present study.…”
Section: Temporal Profile Of K V Channels: Voltage-dependence and Kinmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, using rabbit pial arteries, our laboratory has shown (28,35) that acute exposure of vascular smooth muscle to the blood component oxyhemoglobin can cause internalization of K V 1.5 via a mechanism involving protein tyrosine kinase activation. Others have additionally demonstrated that mRNA and protein levels of K V 2.2 channels were decreased in basilar arteries from a canine SAH model (31). Further studies are required to determine whether K V channel suppression or additional mechanisms contribute to enhanced pressure-dependent depolarization of parenchymal arteriolar myocytes in SAH animals.…”
Section: Discussionmentioning
confidence: 99%
“…Membrane potential depolarization caused by a decrease in Ca 2+ spark-induced transient BK currents would be predicted to cause an increase in the open-state probability of VDCCs and combined with enhanced VDCC expression would increase global cytosolic Ca 2+ leading to enhanced contraction of cerebral artery myocytes. Additional mechanisms such as decreased voltage-dependent potassium (K V ) channel expression (Jahromi et al, 2008a) and activity (Ishiguro et al, 2006;Koide et al, 2007;Quan and Sobey, 2000) and increased protein kinase C activity (Nishizawa et al, 2000) are also likely to contribute to enhanced cerebral artery constriction after SAH.…”
Section: Discussionmentioning
confidence: 99%